2022
DOI: 10.21203/rs.3.rs-1990696/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New Sb 2 Se 3 based solar cell for achieving high efficiency -Theoretical modeling

Abstract: In this paper, we presented a numerical study of a CdS/Sb2Se3 mono junction solar cell (SC) using the SC Capacitive Simulator (SCAPS-1D). We validated an experimental work using a variety of Sb2Se3 experimental parameters, and the results showed excellent agreement between numerical and experimental J-V curves, yielding a PCE of 7.54% .To continue, we analyzed the impact of Sb2Se3 thin layer thickness, charge carrier concentration, bulk defect density, and interface defect (CdS/Sb2Se3) on solar cell characteri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ferdous et al 13 Raman et al used the architecture Al/CdS/Sb 2 Se 3 /Mo and the final PCE they obtained is 28.25%, V oc is 0.86 V, J sc is 37.90 mA/cm 2 , and FF is 86.84%. 14 Daoudi et al have reported PCE of 28.08%, FF of 88%, V oc of 1.07 V, and J sc of 29.53 mA/cm 2 . 15 With the structure CZTS/WS2/In2Se3, Kumar Dakua P et al have obtained a PCE of 22.96%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ferdous et al 13 Raman et al used the architecture Al/CdS/Sb 2 Se 3 /Mo and the final PCE they obtained is 28.25%, V oc is 0.86 V, J sc is 37.90 mA/cm 2 , and FF is 86.84%. 14 Daoudi et al have reported PCE of 28.08%, FF of 88%, V oc of 1.07 V, and J sc of 29.53 mA/cm 2 . 15 With the structure CZTS/WS2/In2Se3, Kumar Dakua P et al have obtained a PCE of 22.96%.…”
mentioning
confidence: 99%
“…The absorber's photogenerated excitons can reach the interfaces owing to their low binding energy and long diffusion lengths. In Figure5(A)-(D), the CuSbS 2 layer thickness varies from 0.05 μm to 0.2 μm and is plotted along the x-axis, and the carrier concentration varies from 10 16 cm À3 to 10 19 cm À3 and plotted along the y-axis 14,…”
mentioning
confidence: 99%